South Asia's Turn : Policies to Boost Competitiveness and Create the Next Export Powerhouse - Lopez-Acevedo, Gladys (Washington, DC: World Bank, 2016)
South Asia has a huge need to create more and better jobs for a growing population – especially in the manufacturing industries where it is underperforming as compared to East Asia. The report examines three critical and relatively understudied drivers of competitiveness: Economies of agglomeration: firms and workers accrue benefits from locating close together in cities or clusters through urbanization and localization. Participation in global value chains: stronger competitive pressures weed out least productive firms while others improve by gaining access to new knowledge and better inputs. Firm capabilities: in order to operate close to what would be considered optimum efficiency levels given the prevailing factor prices and thus employ South Asia’s abundant labor.